A Review of David Sloan Wilson's Evolution for Everyone and Darwin's Cathedral - Hinshaw, John (2008)
A Review of David Sloan Wilson, Evolution for Everyone: How Darwin’s Theory Can Change the Way We Think about Our Lives. Delcacort Press, 2007. 400 pages. David Sloan Wilson, Darwin’s Cathedral: Evolution, Religion and the Nature of Society. Chicago: University of Chicago Press, 2002. 268 pages
Keywords: Rezension